2019
DOI: 10.1007/s10270-019-00724-1
|View full text |Cite
|
Sign up to set email alerts
|

Model execution tracing: a systematic mapping study

Abstract: Model Driven Engineering is a development paradigm that uses models instead of code as primary development artifacts. In this paper, we focus on executable models, which are used to abstract the behavior of systems for the purpose of verifying and validating (V&V) a system's properties. Model execution tracing (i.e., obtaining and analyzing traces of model executions) is an important enabler for many V&V techniques including testing, model checking, and system comprehension. This may explain the increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Then, the traces are collected and used for offline analysis and debugging. Hojaji et al [44] surveys the existing work in the context of model execution tracing. Examples of existing work and MDD tools supporting trace analyses via code instrumentation include [34,38,43,48,49,83].…”
Section: Model-level Debugging On the Target Platformmentioning
confidence: 99%
“…Then, the traces are collected and used for offline analysis and debugging. Hojaji et al [44] surveys the existing work in the context of model execution tracing. Examples of existing work and MDD tools supporting trace analyses via code instrumentation include [34,38,43,48,49,83].…”
Section: Model-level Debugging On the Target Platformmentioning
confidence: 99%
“…6. Related Work [Hojaji et al 2019] presents a systematic mapping study regarding model execution trace. Model execution trace as defined in the study is a mechanism to capture enough relevant information related to the ExM during its execution for later analysis.…”
Section: Expected Contributionsmentioning
confidence: 99%
“…The first notable difference from our study is scope. While [Hojaji et al 2019] aims to characterize the use of model tracing for executable models, we are aiming for characterize the use of ExM for SoS architectural evaluation. The resulting contributions are different because the areas of interest are also different (model tracing and SoS architectural evaluation).…”
Section: Expected Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practical relevance and importance of the research problem has been well demonstrated as being critical for design science research [24]. To ensure that our design objectives are consistent with prior research, we conducted a systematic mapping study in the field of model tracing, which has already been published in [25]. We aim to further disseminate the contributions of this effort in peer review scholarly publications.…”
Section: Introductionmentioning
confidence: 99%